Analysis and control of issues that delay pharmaceutical projects - Jigeesh, Nasina; Rao, Nallam Sai Nandeswara (Business: Theory and Practice, 2015)
Every project will have certain objectives and service levels to be achieved. The success of a project depends on several dimensions like time, cost/budget, quality, etc. and managing a project involves completing the project within time, within budget and with quality to satisfy the users. Because of the significance of health, pharmaceutical companies realized the importance of project management methods and techniques to make available the life saving drugs in time to the needy patients and hospitals. In literature, there is meager information about pharmaceutical project management oriented towards analysis of issues and factors that contribute to the failure or success of projects. This study attempts to analyse different issues that contribute to time delays in pharmaceutical product-based projects, group them under a finite set of prominent factors and identify remedial measures to control those delays. The feedback of project people of some big pharmaceutical firms of Indian sub-continent was collected for this purpose. Exploratory factor analysis (EFA) has been used to reduce the reasons for time delays to a limited number of prominent factors and the EFA model has been further examined by confirmatory factor analysis (CFA) for its validation. Remedial measures under each factor of time delays have been gathered and a framework designed to mitigate the time delays in pharmaceutical projects. The derived factors that delay the pharmaceutical projects include resource, monitoring & control, scheduling and planning problems. Important remedial measures like blended resource approach, estimation and forecast of shortage of labour and skills, regular quality training, etc. have been recommended.